A Comparison of Performance between TFRC and UDP over a Mobile IP Network - Al-Zoubi, Malek Mohammed Saleh (2010)
In this project we will study three performance metrics (packet loss, packet delay and jitter) of two different transport layer protocols over a Mobile IP Network. The researcher will be implementing TFRC and UDP in the Mobile IP Network, to identify which protocols could support mobility. Network Simulation NS-2 was proposed for implementing previous items and to present and interpret the results.